Small-scale food processing : a directory of equipment and methods - Azam-Ali, Sue; Judge, Emma; Fellows, Peter; Battcock, Mike (ITDG Publishing, 2003)
This guide provides development workers and small-scale entrepreneurs with the basic information and advice that they need to set up a small-scale food processing enterprise. Part one considers the food processes that are suitable for different crops including fruit and vegetable products; cereal and pulse-based products; milk and milk products, and meat and fish products. Part two is an annotated directory giving the appropriate equipment needed to process a particular food, an index of manufacturers, the approximate costs and the names and addresses of manufacturers. The potential uses of various equipment is examined and much of the equipment is clearly illustrated.